Epha2 sirna silencing on malignant glioma cells - Azman , Amy Shafinas (2017)

(untitled)
Malignant glioma is one of the most aggressive type of solid tumours which is highly fatal with median survival rate of only 9-12 months. Recently, overexpression of EphA2 has been correlated with the development and tumour progression of malignant glioma. In order to examine the role of EphA2 in malignant glioma cells, inhibition of EphA2 gene expression was carried out using small interfering RNA (siRNA). In this study, siRNA targeting EphA2 gene was used to transfect U87 cells in vitro at three different concentration 12.5 nM, 25 nM and 37.5 nM. Real-Time PCR was used to analyse the EphA2 gene expression levels followed by MTS assay in order to examine the changes in cell viability of U87 cells. Evaluation of the gene expression showed that, significant inhibition of the EphA2 gene expression was observed in groups of cells treated with all 3 concentration of siRNA (p<0.05). The highest knockdown percentage of EphA2 gene was observed at concentration of 12.5 nM (73.6%), followed by 37.5 nM (63.1%) and 25 nM (45%). Based on MTS assay analysis, a decline in cell viability of U87 cells was observed in groups treated with EphA2 siRNA 25 nM and 37.5 nM after 48 hours post transfection. Reduction of 50.1 % and 22.2 % of U87 cells viability was observed in cells treated with EphA2 siRNA 25 nM and 37.5 nM respectively. Recent evidences have shown that EphA2 significantly involves in mediating viability activities of malignant glioma cells. Nevertheless, in this study, the correlation between inhibition of U87 cells viability and EphA2 gene expression knockdown was found not to be significant. In conclusion, this study demonstrated that transfection with all three concentration of EphA2-siRNAs significantly inhibited EphA2 expression at the mRNA level, however it did not consistently suppresses the viability of U87 cells.